Environmental Law Enforceent Against Plastic Waste Disposal Based on Law Number 18 of 2008 Concerning Waste Management - Dian Apriandini; Tanti Nur Ainun Azizah; Kartika Chandra Kirana; Muhammad Falih Abdi Nugroho (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2024)
Environmental problems that have existed from the past until now are waste, especially plastic waste. Based on data obtained from the Indonesian Plastic Industry Association (INAPLAS) and the Central Statistics Agency (BPS), plastic waste in Indonesia reaches 64 million tons / year of which 3.2 million tons are plastic waste disposed of into the sea. Of course, this problem is a threat to marine ecosystems, the threat of plastic waste can cause damage to human health and even potentially damage marine ecosystems and have an impact on climate change. Law No.18 of 2008 concerning Waste Management in preventing these problems, it is necessary to carry out supervisory efforts by law enforcement officials in the community. However, it was found that supervision efforts in the field as an act of prevention were not carried out optimally, the sanctions applied were not firm, making people not obey the laws that had been made. Environmental law enforcement is carried out with three legal instruments, namely administrative, civil and criminal sanctions. Indonesia needs to learn from developed countries, such as neighboring Singapore, Indonesia should apply the rule of law firmly, considering that efforts to protect the environment are fundamental to creating a comfortable place in the country. In protecting the environment of the State of Indonesia, the government should act decisively in enforcing its laws and implementing new legal rules in the form of fines that can be applied in the community and should be a priority for the state to keep the country free from plastic waste in the oceans. Key Words: Indonesian, Law Enforcement, Plastic Waste